Evaluation of thinning behaviour under the influence of plastic hardening and surface friction during small punch test - Pandit, Sarthok Chandra; Nasrul Azuan, Alang; Ferdous, I. U.; Juliawati, Alias; Mohd Firdaus, Hassan; Asnul Hadi, Ahmad (Gruppo Italiano Frattura, 2025)
Understanding the deformation response of the material involving thinning under small punch loading is vital to ensure structural integrity. This paper systematically investigates the effects of plastic hardening on the thinning process under different levels of surface friction between the punch, die and specimen. The small punch test conditions are modeled using Finite Element (FE) software of Abaqus. An axisymmetric model with a bi-linear constitutive material model incorporating different plastic hardening slopes is employed. Furthermore, the Coulomb’s friction coefficient between the disc-shaped specimen and the punch as well as the die varies between 0 (frictionless) to 0.7. The study found that the effect of plastic hardening on thinning process is negligible. On the other hand, the effect of thinning at the center of the specimen is significant under frictionless surface conditions. Thinning is observed to be dominant during the membrane stretching and plastic instability deformation stages. As the surface friction increases, the resistance to sliding deformation decreases. As a result, tensile instability is predicted at the location offset from the center of the specimen. Future efforts to model material behaviour and determine mechanical properties using small punch load conditions must consider the effects of friction.